Analysis of nonlinear stratified convective flow of Powell-Eyring fluid: Application of modern diffusion. (October 2020) - Jabeen, Iffat; Farooq, Muhammad; Rizwan, Muhammad; Ullah, Roman; Ahmad, Shakeel
The stratification phenomena have great importance in fishery management, insufficiency of dissolved oxygen in the lower parts of lakes, rivers and ponds, and phytoplankton populations. Thus the present article examines vital role of stratification phenomena in Powell-Eyring fluid flow due to inclined sheet which is stretched in a linear way. Collaboration of Cattaneo-Christov heat and mass flux model instead of Fourier Law of heat conduction is also accounted. Interpretation of heat transport is carried out with heat generation/absorption. Thermal stratification supports heat transport. Chemical reaction and solutal stratification also helped out mass transport. Non-linear governing equations with partial derivatives are converted into ordinary differential equation with the help of similarity transformations. Homotopic method is applied to solve arising dimensionless governing equations. Pertinent parameters and their physical behavior are displayed graphically. Drag force coefficient is also examined graphically. In culmination, substantial parameters of radiation and heat generation/absorption raised the temperature field while thermal relaxation time and solutal relaxation time parameters lower the temperature and concentration fields, respectively.